Portugal : First Review Under the Extended Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Macroeconomic imbalances are large, and structural problems are deep-rooted in Portugal. The new government's strong commitment to program implementation is encouraging. Fiscal performance so far demonstrates the need to refocus the fiscal strategy on strong expenditure control, as envisaged under the program. To support activity, it is crucial to prevent an excessively rapid deleveraging of the banking sector. Ultimately, the success of the program hinges on opening up the economy and improving competitiveness. The European Council's renewed support enhances prospects for the program's success.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet